Ջոն Ռոուլսի «Արդարության տեսությունը» - Հ. Դ. Թադևոսյան (ՀՀ ԳԱԱ հրատ.)
Американским философом Джоном Ролзом были разработаны два принципа справедливости, которые на его взгляд, должны составлять одну из основ государств и способствовать защите прав и свобод граждан. American philosopher John Rawls has developed two principles of justice, which in his opinion make up one of the basis of the state and favour the defense of rights and liberties of the citizens. Of no less interest is his theory of creating a state, including four stages of formation per se.
Keywords: B Philosophy; Psychology; Religion; B Philosophy